Timing influenced force directed floorplanning - Youssef, H. (1995)
We present a timing driven floorplanning program for general cell layouts. The approach used combines quality of force directed approach with that of constraint graph approach. A floorplan solution is produced in two steps. First a timing and connectivity driven topological arrangement is obtained using a force directed approach. In the second step, the topological arrangement is transformed into a legal floorplan. The objective of the second step is to minimize the overall area of the floorplan. The floorplanner is validated with circuits of sizes varying from 7 to 125 blocks